Antiretroviral Prophylaxis: A Digestive Complication to Know. Issue 12 (29th December 2021) - Lemoine, Anaïs; Michot, Joëlle; Viala, Jérôme; Tounian, Patrick; Dollfus, Catherine
Abstract: An 8-year-old child experienced abdominal pain and melena due to duodenal and ileal ulcerations throughout antiretroviral prophylactic treatment after a needlestick injury. Mild to moderate adverse effects often occur with lamivudine and zidovudine, but more severe adverse effects such as intestinal ulcers resulting in melena after a prophylactic antiretroviral treatment may question the safety of the current guidelines.